Centimeter-Scale Pillared-Layer Metal–Organic Framework Thin Films Mediated by Hydroxy Double Salt Intermediates for CO 2 Sensor Applications - Kim, Ki-Joong; Ellis, James E.; Howard, Bret H.; Ohodnicki, Paul R. (ACS applied materials & interfaces, 2021)
Fabrication of metal-organic framework (MOF) thin films over macroscopic surface areas is a subject of great interest for gas sensor application platforms such as optics and microelectronics. However, a direct synthesis of MOF films at ambient conditions, in particular pillared-layer MOF films due to their anisotropic structures, remains a significant challenge. Herein, we demonstrate for the first time a facile construction of dense and continuous pillared-layer MOF thin films on a centimeter scale via an aluminum-doped zinc oxide template and hydroxy double salt (HDS) intermediates at room temperature. A series of Cu(II)-based pillared MOFs with different 1,4-benzenedicarboxylic acid (bdc) ligands were explored for optimizing MOF film formation for CO sensor applications. Nonpolar ligands with lower water solubility preferentially formed crystalline pillared MOF structures from HDS intermediates. A Cu (ndc) (dabco) (ndc = 1,4-naphthalene-bdc; dabco = 1,4-diazabicyclo[2.2.2]octane) MOF demonstrated the most dense and uniform film growth with micrometer thickness over one square centimeter area. This synthetic approach for growing Cu (ndc) (dabco) MOF thin films was successfully translated toward two sensing platforms: a quartz crystal microbalance and an optical fiber sensor. These Cu (ndc) (dabco) MOF-coated sensors displayed sensitivity toward CO and response/recovery time on the scale of seconds, even at moderate humidity levels. This work provides a road map for producing continuous and anisotropic crystalline MOF thin films over a centimeter scale area on various substrates, which will greatly facilitate their utilization in MOF-based sensor devices, among other applications.